The Impact of Divorce on the Soul of Children and Concrete Solutions from an Islamic Perspective - Muzaqi, Alwi (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2024)
This study examines the impact of divorce on the psychological, social, and academic conditions of children from an Islamic perspective and offers concrete solutions to reduce its negative impacts. Using a qualitative-descriptive approach with the literature study method, this study analyzes various sources, including academic journals, statistical reports, and fiqh books related to Islamic family law. Data were collected through literature review and analyzed with the concept of maqasid al-shariah to identify post-divorce child protection strategies. The results of the study show that divorce can cause emotional disturbances, anxiety, and decreased academic achievement in children. Therefore, support from parents, extended family, schools, and the community is very necessary. Islamic values-based mediation, post-divorce counseling, and an inclusive approach to education are key solutions in helping children cope with these changes. This research emphasizes the importance of a holistic approach in dealing with the impact of divorce for the future well-being of children.